Islamic Legitimacy in a plural Asia - Reid, Anthony 1939-; Gilsenan, Michael (Routledge comtemporay asia series, 2007)
A global debate has emerged within Islam about how to coexist with democracy. This book places the debate in a specifically Asian context, showing how Muslims in Asia have adapted flexibly and creatively to the pluralism with which they have lived, and are likely to continue to do so.